KEANEKARAGAMAN TUMBUHAN MANGROVE DI TAMAN NASIONAL BALI BARAT - Arinasa, Ida Bagus Ketut (Buletin Kebun Raya, 2012)
The diversity of mangrove at West Bali National Park has not been reported completely. The exploration was conducted from 12 - 16 June, 2011 from Banyuwedang to Gilimanuk and from Gilimanuk to Sumbersari-Melaya mangrove forests. The result showed that 18 families consist of 21 genera and 28 mangrove species were recorded at West Bali National Park, these are 11,5% of the Indonesian mangroves.